Energy droughts from variable renewable energy sources in European climates. (September 2018) - Raynaud, D.; Hingray, B.; François, B.; Creutin, J.D.
Abstract: The increasing share of variable renewable energy sources in the power supply system raises questions about the reliability and the steadiness of the production. In this study, we assess the main statistical characteristics of "energy droughts" for wind, solar and run-of-the-river hydro power in Europe. We propose two concepts of energy droughts, considering either: Energy Production Droughts (EPD) as sequences of days with low power production or Energy Supply Droughts (ESD) as sequences of days with a high production/demand mismatch. Using a set of adhoc weather-to-energy conversion models, we characterize energy droughts in 12 European regions from 30-yr series of daily wind, solar, hydro power and energy demand. The characteristics of EPD are very different between sources with short but frequent wind power droughts and rare but long hydro power ones. Solar power droughts are very region-dependent with much longer droughts in Northern Europe. ESD are next characterized in a 100% renewable energy scenario. The features of EPD and ESD differ significantly, highlighting the interplay with the energy demand. Moreover, both duration and frequency of energy droughts decrease when mixing energy sources or when some storage capacity balances the temporal production/demand mismatch. Highlights: Energy droughts are defined as periods of low production or high production/demand imbalance. Energy droughts present various characteristics within Europe and between energy sources. The fluctuations of the energy demand impact energy droughts especially for solar and hydro power. Using several energy sources in an energy mix reduces the frequency and the duration of energy droughts. Small storage systems limit wind power droughts and Southern Europe solar power droughts.